Uji Efektivitas Ekstrak Kulit Manggis terhadap Pertumbuhan Jamur Malassezia furfur - Susanto, Inneke Kusumawati; Pasaribu, Donna Mesina Rosadini; Laurensia Charlina Nova Sambut (Jurnal MedScientiae, 2025)
Background Mangosteen is one of the medicinal plants that has long been known in Southeast Asia, with its skin having various of properties, including antibacterial, antifungal, anti-inflammatory, and antioxidant. Mangosteen skin in traditional medicine is used to cure various diseases. One of the fungi that can cause skin disease in human is Malassezia furfur, which is a lipophilic fungus and part of the normal skin microflora. Objective: This study aims to determine and prove whether mangosteen skin extract has antifungal activity against Malassezia furfur. Method: This study used an experimental method to test the antifungal activity of mangosteen skin extract. Testing was carried out using the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and diffusion methods to measure the inhibitory power against Malassezia furfur at various extract concentrations. Results: The results showed that mangosteen skin extract has antifungal activity against Malassezia furfur. The extract concentration that gave the greatest inhibitory power was 100%, while the lowest concentration that showed inhibitory power was 20%. Conclusion: Mangosteen peel extract has been proven to have antifungal activity against Malassezia furfur, with a concentration of 100% providing the greatest inhibitory effect, while a concentration of 20% still shows an inhibitory effect, but weaker.